O poder econômico das corporações transnacionais e seus impactos socioambientais na sociedade consumocentrista - Bonissoni, Lucas Dalmora (2020)
The economic power that transnational corporations hold directly reflects on consumer-centric society. Its performance is highlighted and generates social and environmental impacts on society that are beyond the control of States. These, weakened, are unable to meet all the demands and needs of humanity, whether due to incapacity or even a lack of priority in their policies. The consequences of the phenomenon of globalization and technological advances in recent decades have led to a transformation in pre-established models, in particular, the protection of consumer rights. In this context, the present dissertation aims to investigate the exercise of economic power by transnational corporations and their socio-environmental impacts on consumer-centric society, under the analysis of the principle of solidarity and the theory of environmental degrowth, with the aim of verifying the consequences of the exercise unregulated of this power to human life and the environment. The study is linked to the line of research on Social Relations and Dimensions of Power of the Master's Program in Law at the University of Passo Fundo UPF and is based on the following question as a problematic proposal to be investigated: how the economic power of transnational corporations impacts society consumer-centric? It is not news that globalization was decisive in the ease with which goods and services became accessible from anywhere in the world. This contributed to the rise of transnational corporations, which, acting with the objective of achieving profit maximization at any cost, began to encourage the manufacturing and marketing of strategically designed products with a determined useful life. Their actions are, in most cases, unconcerned with the environment and sustainability, while they exploit the natural resources of fauna and flora in a way that is unable to regenerate such riches in the same proportion. Furthermore, they settle in countries where tax burden is lower, labor legislation is more flexible and environmental legislation is more lenient. As they fail to obtain the expected profit, they close their doors and migrate to another country, disrupting the entire location of that country, generating unemployment and environmental damage. Today, society is immersed in a worrying scenario, where commerce is growing and the environment bears the consequences of the impacts generated by planned obsolescence, the lack of consumer awareness when it comes to reuse and care for their products and the unregulated and dominant actions of transnational corporations.